User perception, intention, and attitude on mobile advertising. (2017) - Lin, Ching-Wen; Hsu, Yen-Chung; Lin, Ching-Yi
In recent years, due to the rapid development of mobile devices and mobile internet usage, users can access wireless networks to browse information anytime, anywhere. The advertising industry can perform marketing through mobile advertising, and diversity can effectively improve the attractiveness of such advertising. According to the research findings, perceived usefulness, irritation, and credibility were major factors affecting the reuse intention of mobile advertising. Moreover, users should be encouraged to trust mobile advertising and also believe that getting mobile advertising is useful. Coupled with the advantage brought by its low cost, mobile advertising will be a major marketing method. It was expected that the findings could be a reference for the mobile advertising industry in the design of mobile advertising.